A Decomposition of the Atmospheric and Surface Contributions to the Outgoing Longwave Radiation. Issue 20 (12th October 2022) - Huang, Han; Huang, Yi
Abstract: The outgoing longwave radiation ( OLR ), which consists of the thermal radiation from both the atmosphere and surface, is of critical importance to the Earth radiation energy budget. To understand the global OLR distribution, it is important to quantify the varying atmospheric and surface contributions. In this work, we present such a quantification using radiative transfer computations based on global reanalysis atmospheric data. By dissecting the OLR simulated following the radiative transfer equation, we quantitatively measure the layer‐wise atmospheric contributions to OLR and compare it to the surface contribution in different spectral bands. One focus of this study is on the OLR in the far‐infrared ( FIR ), for which new satellites are expected to provide unprecedented measurements. We find that around 45% of the global mean OLR is radiated in the FIR and in polar regions the FIR contribution can increase to 60%. Our vertical decomposition of OLR discloses that although the atmospheric contribution generally surpasses the surface contribution, the enhanced FIR contribution in the polar regions mainly results from a relatively stronger surface (as opposed to atmospheric) contribution. This is allowed by the opening of the atmospheric window in the FIR in these extremely dry regions. Our analysis also reveals that the tropopause layer makes a minimum contribution to the OLR, which may be a unique spectroscopic feature of the Earth atmosphere. Clouds are found to reduce the atmospheric contribution in the FIR while enhancing it in the mid‐infrared. Plain Language Summary: The Earth emits infrared radiation toward space and the total amount of emitted radiation, called outgoing longwave radiation ( OLR ), plays a fundamental role in Earth's energy budget. We quantify the atmospheric contribution to OLR at different heights, with a focus on the radiation energy in the far‐infrared (the spectral region with wavelength longer than 15 μ m $μ m$ ). Combining the spectral, vertical, and geographic perspectives, our analysis identifies the critical atmospheric layers that account for the OLR in different spectral ranges. Our results affirm the importance of far‐infrared spectrum for the Earth radiation balance and reveal that the geographic variation of the OLR in far‐infrared is mainly driven by a varying surface contribution. Key Points: The higher far‐infrared fraction of the outgoing longwave radiation in polar region is due to stronger surface contribution The atmospheric layer around the tropopause makes a minimum contribution to the outgoing longwave radiation Cloud radiative effect reduces the atmospheric contribution in far‐infrared and increases it in the mid‐infrared